Birth weight and its association with blood pressure and nutritional status in adolescents - Vanessa Roriz Ferreira; Thiago Veiga Jardim; Thais Rolim Póvoa; Karla Lorena Mendonça; Flávia Noggueira Nascente; Carolina Sousa Carneiro; Weimar Sebba Barroso; Polyana Morais; Maria Gondim Peixoto; Ana Luiza Lima Sousa; Paulo Cesar Brandão Veiga Jardim (Elsevier, 2018)
Objective: The management of children with low birth weight is not the same in countries with different resources. The authors assessed the association of birth weight with blood pressure and nutritional status in a representative sample of adolescents from a Brazilian state, aiming to identify possible consequences of these differences. Methods: A cross-sectional school-based study was conducted with adolescents (12-18 years) enrolled in public and private schools. Birth weight, office blood pressure, home blood pressure measurements, and nutritional status (body mass index, height z-score for the age, and waist circumference) were assessed. The association of birth weight with the outcomes (blood pressure, height, body mass index, and waist circumference) was studied through univariate and multivariable linear regression models. Results: A total of 829 adolescents with a mean age of 14.6 ± 1.62 years were included; 43.3% were male, and 37.0% from private schools. The prevalence of low birth weight was 8.7%. Mild low height prevalence was higher among those adolescents with low/insufficient birth weight when compared to those with normal/high birth weight (11.7 vs. 4.2%; p < 0.001). In the multiple linear regression analysis, for each increase of 100 g in birth weight, height increased by 0.28 cm (95% CI: 0.18-0.37; p < 0.01). Birth weight did not influence office blood pressure and home blood pressure, body mass index, or waist circumference of adolescents. Conclusions: Birth weight was directly associated to height, but not associated to blood pressure, body mass index, and waist circumference in adolescents from an urban area of a developing country. Resumo: Objetivo: O manejo de crianças com baixo peso ao nascer não é o mesmo em países com diferentes recursos. Investigamos a associação do peso ao nascer com a pressão arterial e o estado nutricional em uma amostra representativa de adolescentes de uma capital brasileira com o objetivo de identificar possíveis consequências destas diferenças. Métodos: Estudo transversal de base escolar conduzido com adolescentes (12-18 anos) matriculados em escolas públicas e privadas. Investigou-se o peso ao nascer, a pressão arterial, e o estado nutricional, por meio do índice de massa corporal, do escore z de estatura para idade e da circunferência da cintura. Resultados: Um total de 829 adolescentes com uma idade média 14.6 ± 1.62 anos foram incluídos, 43.3% do sexo feminino e 37.0% de escolas privadas. A prevalência de baixo peso ao nascer foi 8.7%. Baixa estatura leve foi mais prevalente nos adolescentes com peso ao nascer baixo/insuficiente (11.7 × 4.2% - p < 0.001). Na análise de regressão linear múltipla, para cada aumento de 100 g no peso ao nascer, a estatura aumentou em 0.28 cm (IC 95% = 0.18-0.37; p < 0.01). O peso ao nascer não influenciou a pressão arterial (casual e residencial), o índice de massa corporal e a circunferência da cintura dos adolescentes. Conclusões: O peso ao nascer esteve diretamente associado à altura, mas não associado à pressão arterial, índice de massa corporal e circunferência da cintura em adolescentes de uma área urbana de um país em desenvolvimento. Keywords: Birth weight, Body mass index, Waist circumference, Height, Blood pressure, Palavras-chave: Peso ao nascer, Índice de massa corporal, Circunferência da cintura, Estatura, Pressão arterial